Rapid weight gain in early life is associated with central precocious puberty in girls, not in boys - a nationwide population-based study in Korea - Choe, Yunsoo; Cha, Jong Ho; Kim, Yun Jin; Choi, Jinjoo; Lee, Kyeongmi; Kim, Nayoung; Na, Jae Yoon; Yang, Seung (Frontiers in Endocrinology, 2023)
Objectives: This study aimed to investigate the effect of rapid weight gain (RWG) on the incidence of central precocious puberty (CPP) using nationwide population-based data. Methods: A total of 253,967 children (101,841 boys and 152,126 girls) who underwent regular health consultations under the National Health Insurance Service from 2007 to 2017 were followed up until the age of 10 years for boys and 9 years for girls. We calculated differences in the weight z scores from 4–6 months to 9–12 months (infancy) and from 9–12 months to 18–24 months or 30–36 months (toddlerhood) using the lambda-mu-sigma method. The population was subdivided into four groups: RWGinf/tod (infancy > + 0.67 standard deviation score [SDS], toddlerhood > 0 SDS), RWGinf (infancy > + 0.67 SDS, toddlerhood < 0 SDS), RWGtod (toddlerhood > + 0.67 SDS), and control (no RWG). The diagnosis of CPP was based on the diagnostic codes of the International Classification of Diseases 10th revision and the prescription of gonadotropin-releasing hormone agonists. The cumulative risk of CPP based on age was analyzed using Kaplan–Meier survival curves, and the association between the RWG groups and CPP was assessed using multivariate logistic regression analysis. Results: CPP was diagnosed in 268 boys and 9,225 girls. For the girls, the CPP-free probability was the highest in the control group, followed by the RWGtod, RWGinf, and RWGinf/tod groups (log-rank p < 0.001). However, the incidence of CPP did not vary significantly for the boys. Compared to the control group, the other groups had a higher risk of CPP in girls (RWGinf/tod: adjusted odds ratio [aOR] 1.35, 95%, confidence interval [95% CI] 1.13–1.62; RWGinf: aOR 1.25, 95% CI 1.13–1.38; and RWGtod: aOR 1.18, 95% CI 1.09–1.28). Conclusions: This nationwide population-based study demonstrated that any RWG from birth to 3 years of age contributed to an increased risk of CPP in girls but not in boys. Girls who experienced RWG during both infancy and toddlerhood had the highest risk of developing CPP. These findings suggest that early detection and appropriate management of excessive weight gain in early life may be important for preventing CPP in girls.